On Freezing Effects - Gallego, Ángel (IBERIA: An International Journal of Theoretical Linguistics, 2010)
This paper discusses the nature of Rizzi’s (2006; 2007) Criterial Freezing, a mechanism yielding island effects on XPs moving into edge positions within the Left Periphery to satisfy dedicated ‚criteria‛. Contrary to Rizzi’s (2006) feature checking implementation, it is claimed that freezing, as originally outlined in Chomsky’s 2000; 2001 Probe-Goal framework, is restricted to purely formal features of the Case/agreement systems, criterial formatives (e.g., [topic], [focus], [wh]) being irrelevant for minimality purposes. Consequently, it is argued that Criterial Freezing is best regarded as an interface constraint precluding XPs from being assigned multiple interpretations of the same type, for legibility/convergence reasons ultimately related to the Principle of Full Interpretation.